Enhanced removal of naproxen from wastewater using silica magnetic nanoparticles decorated onto graphene oxide; parametric and equilibrium study. Issue 15 (13th October 2018) - Mohammadi Nodeh, Mohammad Kazem; Radfard, Morteza; Zardari, Liaquat Ali; Rashidi Nodeh, Hamid
ABSTRACT: The present study describes the synthesis of silica and magnetic nanoparticle-decorated graphene oxide (GO-MNPs-SiO2 ) and its application as an adsorbent for the removal of naproxen from wastewater. Nanocomposite was characterized utilizing FT-IR spectroscopy, FESEM microscopy, EDX and XPS spectroscopy. Under the optimum conditions, a high adsorption capacity (31 mg g −1 ) was obtained toward naproxen at pH 5. The adsorption process was evaluated using isotherms; the Freundlich isotherm suggested a multilayer adsorption pattern for naproxen. Free energy confirmed a physisorption mechanism between naproxen and adsorbent. Lastly, the field application was performed in wastewater which obtained high removal efficiency percentages (83–94%).